Leishmania species‐dependent functional duality of toll‐like receptor 2. Issue 11 (22nd July 2019) - Jafarzadeh, Abdollah; Nemati, Maryam; Sharifi, Iraj; Nair, Arathi; Shukla, Divanshu; Chauhan, Prashant; Khorramdelazad, Hossain; Sarkar, Arup; Saha, Bhaskar
Abstract: Toll‐like receptors (TLRs) are a subset of pattern recognition receptors (PRR) in innate immunity and act as a connecting link between innate and adaptive immune systems. During Leishmania infection, the activation of TLRs influences the pathogen‐specific immune responses, which may play a decisive role in determining the outcome of infection, toward elimination or survival of the pathogen. Antigen‐presenting cells (APCs) of the innate immune system such as macrophages, dendritic cells (DCs), neutrophils, natural killer (NK) cells, and NKT cells express TLR2, which plays a crucial role in the parasite recognition and elicitation of immune responses in Leishmania infection. Depending on the infecting Leishmania species, the TLR2 pathways may result in a host‐protective or a disease‐exacerbating response. While Leishmania major and Leishmania donovani infections trigger TLR2‐related host‐protective and non‐protective immune responses, Leishmania mexicana and Leishmania infantum infections are reported to elicit TLR2‐mediated host‐protective responses and Leishmania amazonensis and Leishmania braziliensis infections are reported to evoke a disease‐exacerbating response. These findings illustrate that TLR2‐related effector functions are diverse and may be exerted in a species‐ or strain‐dependent manner. TLR2 agonists or antagonists may have therapeutic potentials to trigger the desired immune response during leishmaniasis. In this review, we discuss the TLR2‐related immune responses during leishmaniasis and highlight the novel insights into the possible role of TLR2‐driven resistance or susceptibility to Leishmania .